Cyber-Physical System Interface for Implantable Esophageal Prosthesis - Ana Magdalena Anghel; Teodora Mîndra (Sensors)
This article presents a Cyber-Physical System Interface (CPSI) for a patented implantable esophageal prosthesis. Designed for in vivo use, the CPSI has been implemented in a MATLAB (version R2021b) simulation environment integrated with real-time data from sensors relevant for monitoring the prosthesis’s physical positioning and environmental interactions, aggregated through an Arduino external system. This setup enables the modeling and analysis of system behaviors in a controlled setting. The paper discusses the sensors, hardware and software components supporting a wide range of applications, and the method chosen for sensor-to-display flow. The case study demonstrates two monitoring system applications: one analyzes the influence of variations in the prosthesis geometry, while the other evaluates the tissue response to the implant. The proposed framework and implementation are highly relevant for a wide range of in vivo implants and related systems.